Mental Concept of Professional Identification in Youth: Part IV - Lyudmila A. Pyankova (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The article introduces the initial psychological and economic conditions for a professional self-identification program for young people as the final component of the constructed mental concept. Interiorization is an internal mechanism and a psychological prerequisite that immanently represents the behavioral scheme of stimulus-response as an integral response in the form of cognitive, axiological, motivational, and behavioral patterns. The preference for internal or external determinants, which are assumed as stimuli, reflects the type of identification, cognitive or affective. These stimuli are in fact economic prerequisites that determine the strategies of the country’s socio-economic development. They create factors for its growth, as well as allow people to realize their intentions as homo economicus, i.e., stable full-time employment, professional skills, long-term career plans, etc. This model can be illustrated by the methods of personnel stimulation and motivation at the level of corporate culture. The proposed algorithm of mental mediation involves stage-by-stage goal-setting, stimulation (external motivations), and group mediation, where there is a gravitation towards the Western, Eastern, or mixed civilizational model, individual mediation, as well as the transfer of motivational interventions to professional groups and their effect on professional behavior. It makes it possible to reduce the resistance to polar civilizational models, i.e., individualism vs. collectivism, in order to follow the existing axiological attraction.